Intra-pyloric botulinum toxin injection improves liquid gastric emptying using 99mTc DTPA scintigraphy: a case report in a 2 years- old girl with idiopathic gastroparesis - Khadijah Sumitro; Andy Darma; Tri Sucianti; Stepanus Massora; Alpha Athiyyah; Reza Ranuh; Subijanto Soedarmo (Asia Oceania Journal of Nuclear Medicine and Biology)
Gastroparesis, characterized by delayed gastric emptying in the absence of mechanical obstruction, is a challenging condition to diagnose and treat in children due to limited pediatric-specific data. This case report presents a 15-month-old girl with recurrent and chronic vomiting since infancy, which worsened upon the introduction of solid foods. Initial diagnostic evaluations, including esophagogastroduodenoscopy (EGD) and upper gastrointestinal contrast study, ruled out structural abnormalities. A gastric emptying scintigraphy (GES) with 99mTc DTPA confirmed significant gastric retention, leading to a diagnosis of idiopathic gastroparesis. Endoscopic intra-pyloric botulinum toxin injection (IPBI) was performed and resulting in significant symptom improvement. Post-procedure assessments revealed improved gastric emptying, with reduced retention at 60 and 180 minutes and a markedly decreased half-time (t1/2) was shown following the procedure. These findings highlight that IPBI may be a promising therapeutic option for pediatric idiopathic gastroparesis unresponsive to standard treatments. Further research is warranted to refine treatment protocols and evaluate long-term outcomes.